Flexibility in Port Planning and Design - Taneja, P.; Ligteringen, H.; Walker, W.E. (European Journal of Transport and Infrastructure Research, 2012)
Recently, flexibility has received much attention from port researchers, designers, and managers. This is because the stability of the competitive environment of the past has been replaced by increasing uncertainty. The current economic crisis and the recent trends in ports and shipping sectors are causing port planners to rethink their approach towards port planning, design, and project evaluation. Attributes such as flexibility and adaptability can provide a port infrastructure system with the capacity to be useful under changing requirements, making it robust in face of uncertainty, lengthening its economic lifetime, and thereby guaranteeing payback on investments. Due to the burgeoning research in the field, new measures, new evaluation methods, and new theories and approaches for incorporating flexibility in large-scale infrastructure design have appeared. Adaptive port planning methods are being advocated in place of traditional planning approaches. ‘Design for obsolescence’ is being suggested as an alternative for ‘building in redundancy’ in port infrastructure design. ‘Flexibility’ and ‘adaptability’ are being added to the list of life cycle properties. Real option methods are being advocated for project evaluation under uncertainty. The objective of this paper is to examine the present trends in the port sector and the current practices in port planning, design, and project evaluation. Having identified the inadequacy of these practices under uncertainty, the paper recommends integrating flexibility in designs and processes. It further suggests that Adaptive Port Planning methods, which include Real Options Analysis for valuing flexibility, are better suited in times of uncertainty than the traditional methods.